Predictors of Urethral Stricture After Transurethral Resection of the Prostate Procedure - Daniel Saputra; Ahmad Agil; Akhmad Mustafa (Faculty of Medicine, Universitas Padjadjaran, 2023)
Transurethral resection of the prostate (TURP) is the most frequently used urology surgical method to manage benign prostate hyperplasia (BPH). Despite the relatively efficacious treatment, urethral stricture (US) may form after TURP. The prevalence of the urethral strictures (US) following TURP ranges from 2.2% to 9.8%. The study aimed to identify the predictors of urethral strictures in patients receiving TURP. This study was a retrospective cohort study on patients underwent TURP in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, between 2015 and 2019. Data were obtained from medical records and urology registry of a minimum 12-month follow-up period. Data on patient demographics, estimated volume of the prostate, total resected prostate, and operating time were extracted. Multiple logistic regression was utilized to determine the odds ratio difference between groups. A total of 451 TURP cases were performed between 2015 and 2019, with 22 (4.87%) cases of post TURP US identified. The mean estimated prostate weight was 45.6 g and resected prostate weight was 20.4 g, with a 0.37 gr/min resection rate. Prostate weight, operating time, and duration of catheterization after surgery were not significantly different statistically. Slower resection rate and smaller resected volume are the statistically significant predictors of increased occurrence of urethral stricture (p<0.05). Lower resection rate is also a predictor for urethral stricture after TURP procedure.